2021
DOI: 10.1002/pc.26369
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of insulation properties of glass fiber fabric/epoxy composites modified by polymeric and inorganic fillers

Abstract: Glass fiber fabric-reinforced epoxy composites (GEC) have some weakness on both thermal insulation and sound absorption insulation, which are very important for many application areas such as aircraft, train, and so on. The main aim of this study is to improve both sound absorbent and thermal insulation properties of GEC by incorporating different fillers such as hollow glass microspheres (HGMs), polystyrene (PS) microfiber membrane, and PS solution. Results show that incorporation of PS solution into glass fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 57 publications
(70 reference statements)
0
6
0
Order By: Relevance
“…The lower λ in the composites may be explained by their greater θ and, therefore, the larger proportion of air in their microstructure. [62][63][64][65] Moreover, the composite with treated fibers had a λ 8.5% lower than the composite with native MW, despite the small differences in their θ and V f-empty . This result demonstrated the importance of keeping the hollow structure of MW for improving the insulation capacity of the composites.…”
Section: Thermal Conductivity Of the Compositesmentioning
confidence: 99%
“…The lower λ in the composites may be explained by their greater θ and, therefore, the larger proportion of air in their microstructure. [62][63][64][65] Moreover, the composite with treated fibers had a λ 8.5% lower than the composite with native MW, despite the small differences in their θ and V f-empty . This result demonstrated the importance of keeping the hollow structure of MW for improving the insulation capacity of the composites.…”
Section: Thermal Conductivity Of the Compositesmentioning
confidence: 99%
“…Glass fiber is a wellknown inorganic reinforcement because it has important engineering applications owing to its thermal and mechanical properties and corrosion resistance, such as in aerospace, automobiles, and civil construction. 1 Calcium carbonate, on the other hand, is used as a filler in polymeric composites mainly for reducing production costs, improving mechanical properties and hardness, and facilitating processing, such as contraction control in the injection process. CaCO 3 efficiency is affected by several factors, such as filler content, particle size, and particle adhesion.…”
Section: Introductionmentioning
confidence: 99%
“…The maximum increase in thermal stability of 26°C was observed for the composites fabricated with addition of 40 wt% HGMs and 8 wt% of carbon fibers. Altay et al 22 observed that the addition of HGMs did not contribute to improving in thermal insulation and sound absorption properties of glass fiber/epoxy composites. The fracture toughness of the epoxy resin composites could be enhanced with the reinforcement of hollow glass microspheres due to the debonding of HGMs particles 10,23,24 .…”
Section: Introductionmentioning
confidence: 99%